2020
DOI: 10.1177/0269881119895518
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy, depression severity and mortality: Data from the Danish National Patient Registry

Abstract: Background: The effects of electroconvulsive therapy are usually estimated from changes in depression scales from studies with relatively small patient samples. Larger patient samples can be achieved from epidemiological registers, which provide information on other social and clinical predictors, results and risks. Aims: To examine whether depression severity predicts the use of electroconvulsive therapy, risk of re-hospitalization, suicidal behaviour and mortality following electroconvulsive therapy in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 19 publications
6
33
1
Order By: Relevance
“…10 Our findings are also consistent with a recent study from Denmark, which has a similar universal health care system to Canada, that found age and depression severity increase the likelihood of ECT, while alcohol use, being unmarried, and having low education decrease the likelihood of ECT. 11 These consistent results from a variety of jurisdictions support our hypothesis that ECT use is driven by a combination of appropriate clinical factors and questionable nonclinical factors. Although our study used Canadian data, this finding that enabling resources influence receipt of ECT also likely applies to other health care systems who are seeking to improve equitable access to this important treatment.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…10 Our findings are also consistent with a recent study from Denmark, which has a similar universal health care system to Canada, that found age and depression severity increase the likelihood of ECT, while alcohol use, being unmarried, and having low education decrease the likelihood of ECT. 11 These consistent results from a variety of jurisdictions support our hypothesis that ECT use is driven by a combination of appropriate clinical factors and questionable nonclinical factors. Although our study used Canadian data, this finding that enabling resources influence receipt of ECT also likely applies to other health care systems who are seeking to improve equitable access to this important treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, previous work has pointed out disparities in access to ECT treatment, as evidenced by nonclinical factors such as being unmarried, less educated, black race, and lack of proximity to ECT treatment facilities being associated with lower probability of receiving treatment. 10,11 Understanding the real-world implementation of ECT, and in particular characteristics of patients who do and do not receive it, may help identify populations to specifically target and improve access to ECT. Previous studies in this area have had shortcomings that limited their ability to achieve this goal.…”
Section: Introductionmentioning
confidence: 99%
“…Among physical treatments, electroconvulsive therapy (ECT) is considered clinically to be highly effective for acutely suicidal patients, although research to support long‐lasting suicide‐preventing effects of even repeated ECT is very limited 85,86 . Other neurostimulating treatments, including repeated transcranial magnetic stimulation (rTMS), 87–89 vagal nerve stimulation, 90 and other experimental forms of superficial or deep brain stimulation (DBS), 91 may be effective for the treatment bipolar depression, whereas effects on suicidal behavior in BD patients require testing.…”
Section: Treatmentmentioning
confidence: 99%
“…Two other studies showed higher rates of completed suicide associated with ECT. Jorgensen et al (2020) using the Danish National Patient Registry, examined data of 92,895 patients with single or recurrent depression. They found that 5,004 patients were treated with ECT and that ECT treatment was associated with subsequent risk of completed suicide.…”
Section: Retrospective Studiesmentioning
confidence: 99%
“…They found that 5,004 patients were treated with ECT and that ECT treatment was associated with subsequent risk of completed suicide. Adjustment for the possible confounders decreased the risk, but it remained significant (Jorgensen et al, 2020) (Supplementary Table 2). The increased risk in completed suicide was less with increased severity of depression.…”
Section: Retrospective Studiesmentioning
confidence: 99%